IN VITRO COMPARATIVE EFFECTS OF BIOSIMILAR AND REFERENCE BEVACIZUMAB ON OXIDATIVE STRESS, INFLAMMATION, AND CYTOTOXICITY IN RETINAL PIGMENT EPITHELIAL CELLS - PAENSUWAN, PUSSADEE; KHOTCHARRAT, ROSSUKON; THONGSUK, WANACHAT; LUANGSAWANG, KANIN (International Journal of Applied Pharmaceutics, 2025)
Objective: To compare the effects of the bevacizumab biosimilar (bevacizumab-awwb, MVASI®) and reference bevacizumab (Avastin®) on oxidative stress, inflammation, and cytotoxicity in human retinal pigment epithelial (ARPE-19) cells. Methods: ARPE-19 cells were treated with clinically relevant concentrations of bevacizumab-awwb or reference bevacizumab (0.313 and 0.625 mg/ml) for 24 h. Cell viability was assessed using Alamar blue assay and apoptosis was analyzed by Annexin V-FITC/PI flow cytometry. Intracellular reactive oxygen species (ROS) generation was evaluated by CMH2DCFDA staining and fluorescence quantification. Proinflammatory cytokine secretion (IL-1β, IL-6, TNF-α) was measured using ELISA. Expression of nuclear factor erythroid 2-related factor 2 (Nrf2) and phosphorylation of extracellular signal-regulated kinase 1/2 (Erk1/2) were determined by capillary-based Western blotting. Results: Both bevacizumab-awwb and reference bevacizumab had no significant effects on cell viability or apoptosis induction relative to untreated controls (P>0.05), indicating preserved membrane integrity and absence of cytotoxicity after 24 h exposure. ROS production and secretion of IL-1β, IL-6, and TNF-α remained unchanged, suggesting no oxidative or inflammatory response. Notably, bevacizumab-awwb treatment upregulated Nrf2 expression and Erk1/2 phosphorylation, indicating activation of antioxidant-related signaling pathways. Conclusion: These findings indicate that a clinical dose of bevacizumab-awwb, comparable to its reference biologic, does not induce oxidative stress or inflammation in ARPE-19 cells. Furthermore, it may contribute to oxidative stress modulation through increased Nrf2 expression. Collectively, these results support the use of bevacizumab-awwb as a safe, non-toxic alternative for intravitreal therapy in ophthalmic diseases.